Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

If $$k=\log_2 (\sqrt{9} + \sqrt{5})$$ express $\log_2 (\sqrt{9} - \sqrt{5})$ in terms of $k$.

share|improve this question
    
Hint: $\log_2(9-5)=\log_2((\sqrt{9}-\sqrt{5})(\sqrt{9}+\sqrt{5}))$ –  lemon Aug 24 at 13:23

2 Answers 2

up vote 2 down vote accepted

Adding the logarithms $\log_2{(\sqrt{9}-\sqrt{5})}$ and $\log_2{(\sqrt{9}+\sqrt{5})}$ we get the following:

$$\log_2{(\sqrt{9}-\sqrt{5})}+\log_2{(\sqrt{9}+\sqrt{5})}=\log_2{(\sqrt{9}-\sqrt{5})(\sqrt{9}+\sqrt{5})}=\log_2{(9-5)}=\log_2{4}=\log_2{2^2}=2 \cdot \log_2{2}=2$$

Knowing that $k=\log_2{(\sqrt{9}+\sqrt{5})}$ we have:

$$\log_2{(\sqrt{9}-\sqrt{5})}+\log_2{(\sqrt{9}+\sqrt{5})}=\log_2{(\sqrt{9}-\sqrt{5})}+k$$

Therefore, $$2=\log_2{(\sqrt{9}-\sqrt{5})}+k \Rightarrow \log_2{(\sqrt{9}-\sqrt{5})}=2-k$$

share|improve this answer

Add to both sides the term $\log_2 (\sqrt{9} - \sqrt{5})$, then you have $$ \log_2 (\sqrt{9} - \sqrt{5}) + k = \log_2 (4), $$ so that $$ \log_2 (\sqrt{9} - \sqrt{5}) = 2 - k. $$

share|improve this answer
2  
Add not multiply. –  lemon Aug 24 at 13:24
    
Yuck, what a blunder. Thanks. –  Bennett Gardiner Aug 24 at 13:26
    
The answer from the text book is 2(2-k) –  BillyTeo Aug 24 at 13:29
2  
@BillyTeo well the textbook is wrong. –  lemon Aug 24 at 13:31
    
Thank you lemon. –  BillyTeo Aug 24 at 13:34

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.